EVALUASI PENERIMAAN TEKNOLOGI INFORMASI DI BEBERAPA PERGURUAN TINGGI SWASTA DI KOTA PALEMBANG - nasir, Muhammad; Sahfitri, Vivi (Universitas Bina Darma, 2013)
Information technology is an invaluable tool in solving the problems faced by humans. Utilization of information technology to provide better performance implications on information technology. Information and technologies that support college activities is a valuable asset. College success is usually to understand the advantages and usefulness of information technology to support high-performance university. Unified Theory Of Acceptance And Use Of The Technolgy (UTAUT) Model is a model of information technology acceptance. User acceptance is an important factor affecting the successful implementation of a technology. The study results showed that simultaneous or partially contained a significant and positive relationship between the variables of performance expectancy, effort expectancy, social influence, Behavioral Intention and Behavior Use of the Technology Acceptance variables. While the results of regression analysis obtained by the fact that the contribution of these three variables is 58.9% of the revenues of Information Technology. Keywords:UTAUT Model, User Acceptance, and Information Technology